2019
DOI: 10.1080/0142159x.2018.1544417
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary expertise in medical practice: Challenges of using and producing knowledge in complex problem-solving

Abstract: Purpose: Clarification of interdisciplinary expertise as the ability to deal with the cognitive and epistemological challenges of multi-and interdisciplinary problem-solving-such as in developing and implementing medical technology for diagnoses and treatment of patients in collaborations between clinicians, technicians and engineers-, and of the higher-order cognitive skills needed as part of this expertise. Method: Clarify the epistemological difficulties of combining scientific knowledge, methodologies and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 54 publications
(58 reference statements)
0
18
0
Order By: Relevance
“…With our work, we will encourage researchers to recognize the threats, continue the research about DT in business, and examine the advantages of the digital change. Moreover, in showing a holistic approach to DT research, our results can be regarded as the first step to foster researcher's adaptive expertise to understand and combine results and procedures from different fields (Boon et al 2019). For future research, we encourage a mutual interchange of findings from corresponding research streams, as we showed with our study.…”
Section: Tourismmentioning
confidence: 64%
See 1 more Smart Citation
“…With our work, we will encourage researchers to recognize the threats, continue the research about DT in business, and examine the advantages of the digital change. Moreover, in showing a holistic approach to DT research, our results can be regarded as the first step to foster researcher's adaptive expertise to understand and combine results and procedures from different fields (Boon et al 2019). For future research, we encourage a mutual interchange of findings from corresponding research streams, as we showed with our study.…”
Section: Tourismmentioning
confidence: 64%
“…Research streams on digital transformation from a holistic… may ease the comprehension of complementary conclusions from adjacent fields and foster an interdisciplinary understanding. In emerging topics, expertise is important, as is adaptive expertise, which describes the ability of researchers to understand and combine results and procedures from different fields (Boon et al 2019). Thus, our results can be regarded as the first step towards this ability by showing a holistic approach to DT research.…”
Section: Introductionmentioning
confidence: 93%
“…With that approach in mind, we recommend teachers for implementation develop curricula and programs that are built on contemporary educational philosophy and theory. Especially relevant bodies of work to draw from include those centered on competency-based education 12, 25-27 , interprofessional education and collaboration 28 , and online learning strategies 29 .…”
Section: How To Teach For Implementationmentioning
confidence: 99%
“…Especially relevant bodies of work to draw from include those centered on competency-based education, 12,[25][26][27] interprofessional education and collaboration, 28 and online learning strategies. 29 Teachers for implementation should be strategic but generous with co-learning opportunities for implementation researchers and practitioners.…”
Section: How To Teach For Implementationmentioning
confidence: 99%
“…To participate in multi-disciplinary collaborations, contributors must understand how different perspectives guide varied ways of thinking (Boon et al, 2019 ). These perspectives cause experts from different disciplines to ask different questions, refer to different discipline-specific knowledge, and use diverse methods and technologies to come up with solutions.…”
Section: Learning Goals In Four Dimensionsmentioning
confidence: 99%